Design of High Performance Scroll Microcoils for Nuclear Magnetic Resonance Spectroscopy of Nanoliter and Subnanoliter Samples - Meriam Khelifa; Denis Mounier; Nourdin Yaakoubi (Sensors, 2020)
The electromagnetic properties of scroll microcoils are investigated with finite element modelling (FEM) and the design of experiment (DOE) approach. The design of scroll microcoils was optimized for nuclear magnetic resonance (NMR) spectroscopy of nanoliter and subnanoliter sample volumes. The unusual proximity effect favours optimised scroll microcoils with a large number of turns rolled up in close proximity. Scroll microcoils have many advantages over microsolenoids: such as ease of fabrication and better <semantics>B1</semantics>-homogeneity for comparable intrinsic signal-to-noise ratio (SNR). Scroll coils are suitable for broadband multinuclei NMR spectroscopy of subnanoliter sample.